2022
DOI: 10.1038/s41597-022-01832-2
|View full text |Cite
|
Sign up to set email alerts
|

RedDB, a computational database of electroactive molecules for aqueous redox flow batteries

Abstract: An increasing number of electroactive compounds have recently been explored for their use in high-performance redox flow batteries for grid-scale energy storage. Given the vast and highly diverse chemical space of the candidate compounds, it is alluring to access their physicochemical properties in a speedy way. High-throughput virtual screening approaches, which use powerful combinatorial techniques for systematic enumerations of large virtual chemical libraries and respective property evaluations, are indisp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…A far-reaching effect in the electron-withdrawing and electron-donating ability of functional groups was intended for in order to induce local changes in the electron density on the redox-active carbonyl units of the quinone-based molecules. 45–49 Thus, to cover a sizable chemical space when searching for redox active SIB cathode candidates, we considered nine different R-groups for the functionalization of all of the 170 backbone molecules. These R-groups were –CN, –CF 3 , –COOCH 3 , –F, –Cl, –Br, –CH 3 , –OCH 3 , and –NH 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A far-reaching effect in the electron-withdrawing and electron-donating ability of functional groups was intended for in order to induce local changes in the electron density on the redox-active carbonyl units of the quinone-based molecules. 45–49 Thus, to cover a sizable chemical space when searching for redox active SIB cathode candidates, we considered nine different R-groups for the functionalization of all of the 170 backbone molecules. These R-groups were –CN, –CF 3 , –COOCH 3 , –F, –Cl, –Br, –CH 3 , –OCH 3 , and –NH 2 .…”
Section: Resultsmentioning
confidence: 99%
“…According to this, all the hydrogen atoms that are bonded to the molecular backbone carbon atoms have been consistently substituted with a particular R-group. A far-reaching effect in the electron-withdrawing and electron-donating ability of functional groups was intended for in order to induce local changes in the electron density on the redoxactive carbonyl units of the quinone-based molecules [45][46][47][48][49] . Thus, to cover a sizable chemical space when searching for redox active SIB cathode candidates, we considered nine different R-groups for the functionalization of all of the 170 backbone molecules.…”
Section: Library Generation and Purchasable Compound Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Er and coauthors tested several molecular representations and machine learning models for predicting the DFT-computed aqueous one-step two-electron two-proton redox reaction energies of more than 15,000 redox-active molecule pairs from the RedDB database . They found that structural fingerprints outperform physicochemical descriptors and natural language processing embeddings in encoding the redox chemistry.…”
Section: Deep Learningmentioning
confidence: 99%
“…Such a database is unique for varying oligonucleotides, even though databases of many MM and QM properties exist for other types of molecules, many reported in the same, Scientific Data, journal. Examples of other QM-based datasets published in the same spirit are physico-chemical properties of 31,618 electroactive molecules for development of aqueous redox flow batteries 15 , optimised molecular geometries and thermodynamic data of more than 665,000 biologically and pharmacologically relevant molecules 16 , electronic charge density of crystalline materials from Materials Project database 17 , molecular conformations of 450,000 small- and mid-sized organic molecules 18 , molecular geometries and spectral properties of 61,489 crystal-forming organic molecules 19 , equilibrium conformations for small organic molecules 20 , QM calculations of over 200,000 organic radical species and 40,000 associated closed-shell molecules 21 , all-atom force-field parameters, molecular dynamics trajectories, QM properties, and curated physicochemical descriptors of more than 300 antimicrobial compounds 22 , excited state information of 173,000 organic molecules 23 , conformational energies and geometries of di- and tripeptides 24 , and QM structures and properties of 134,000 small organic molecules 25 .…”
Section: Background and Summarymentioning
confidence: 99%